2003
DOI: 10.1074/jbc.m212556200
|View full text |Cite
|
Sign up to set email alerts
|

Stk10, a New Member of the Polo-like Kinase Kinase Family Highly Expressed in Hematopoietic Tissue

Abstract: The Ste20 family of serine/threonine kinases plays an important role in numerous cellular functions such as growth, apoptosis, and morphogenesis. We have identified a previously cloned but uncharacterized family member termed Stk10, which is a human homolog of murine Lok, a serine/threonine kinase highly expressed in lymphocytes. Northern analysis demonstrated that the Stk10 transcript is present in many tissues, although highest expression levels are seen in hematopoietic cells. Due to close sequence homology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 40 publications
2
47
0
Order By: Relevance
“…Another report indicated that Cdc2/cyclin B purified from recombinant baculovirus-infected cells does phosphorylate and activate Plk1 in vitro (Kotani et al, 1998). More recently, Stk10, a member of the Ste20 serine/threonine kinase family, was shown to phosphorylate Plk1 (Walter et al, 2003). It is unclear, however, how Stk10 is regulated.…”
Section: Introductionmentioning
confidence: 99%
“…Another report indicated that Cdc2/cyclin B purified from recombinant baculovirus-infected cells does phosphorylate and activate Plk1 in vitro (Kotani et al, 1998). More recently, Stk10, a member of the Ste20 serine/threonine kinase family, was shown to phosphorylate Plk1 (Walter et al, 2003). It is unclear, however, how Stk10 is regulated.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of Plx1 by phosphorylation was still required, implying that there must be another kinase that can phosphorylate Plx1 T201 in the xPlkk1-depleted extracts. Both human SLK and Stk10 have been shown to phosphorylate human Plk1 at T210 in vitro and are able to stimulate Plk1 activation in vivo (Ellinger-Ziegelbauer et al, 2000; Walter et al, 2003). It was previously believed that Stk10 could not be the Plk1-activating kinase because the mouse homolog, LOK, was only expressed in lymphatic tissues.…”
Section: Activation and Phosphorylation Of Plksmentioning
confidence: 99%
“…Stk10 is a member of the Ste20 family of serine/threonine protein kinases and similar to the polo-like kinase kinases. It is highly expressed in hematopoietic cells (72).…”
Section: Tslp Signaling Networkmentioning
confidence: 99%